2003
DOI: 10.1007/s00223-001-1069-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fluoride Pretreatment on the Solubility of Synthetic Carbonated Apatite

Abstract: The purpose of this research was to address the following question: How is the solubility of fluoride-pretreated carbonated apatite (CAP) in aqueous acidic media related to the equilibrium solution fluoride and/or the CAP adsorbed fluoride levels? A CAP sample prepared by a precipitation method at 70 degrees C containing approximately 6% carbonate was fluoride-treated (F adsorption from neutral aqueous solutions) to yield a approximately 1000 ppm F CAP and a approximately 3300 ppm F CAP. Metastable equilibrium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…This conclusion is supported by the large deviations with pH when distributions were constructed on the basis of pI OCP instead of pI HA . Approximate calculations also indicated that fluorapatite is not the solubility-controlling phase, but further work on the role of F is certainly required, in the light of recent work [37].…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion is supported by the large deviations with pH when distributions were constructed on the basis of pI OCP instead of pI HA . Approximate calculations also indicated that fluorapatite is not the solubility-controlling phase, but further work on the role of F is certainly required, in the light of recent work [37].…”
Section: Discussionmentioning
confidence: 99%
“…Work in our laboratory [11][12][13][14][15][16][19][20][21][22][23][24] has been focused on developing and applying methods for investigating the solubility behavior of CAPs in acidic aqueous media. Within the time scale of laboratory experiments, CAPs do not follow conventional solubility theory (i.e., the thermodynamic solubility product principle) but exhibit a behavior termed "metastable equilibrium solubility (MES)" [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Within the time scale of laboratory experiments, CAPs do not follow conventional solubility theory (i.e., the thermodynamic solubility product principle) but exhibit a behavior termed "metastable equilibrium solubility (MES)" [12,13]. All apatite preparations investigated to date appear to demonstrate the MES and the MES distribution phenomenon [8,[12][13][14][15][16][19][20][21][22][23][24][25] including CAPs synthesized at various temperatures, possessing different carbonate levels and crystallinities, bone mineral from rats of different ages, and human dental enamel. Recent work has established that, for a given CAP preparation, a relationship may exist between the MES (and the MES distribution) and a MES driving force, which may be expressed in terms of a relevant ion activity product, K MES .…”
Section: Introductionmentioning
confidence: 99%
“…Calcium content was analyzed by the method of Sarkar and Chauhan [1967], phosphate by the method of Gee et al[1954], and carbonate by the micro diffusion method of Conway [1962]. Fluoride content was determined by dissolving a small amount of the F-CAPs with 1 ml of 1M HClO 4 solution, then adjusting to pH 5.0 with NaOH; the final solution being measured with a fluoride ion selective electrode (Radiometer) [Barry et al 2003]. The specific surface area of each F-CAP sample was determined by the BET method with nitrogen as adsorbate (Monosorb, Quantachrome, NY).…”
Section: Methodsmentioning
confidence: 99%